Mental Health since childhood: a social responsability - Reyes Portocarrero, Bertha (2004)
The article stands out the importance of the preparation of the future parents, basing it in its identification and integration like individual people and as couple before conceiving its children, to end that when these they arrive, be developed in an atmosphere that propitiates its mental health. It outlines the use of strategies to be assumed by the future parents in order to wait, to receive and to raise their children in healthy form. It proposes strategies so that the psychologists and professionals of mental health form. It commits and contribute to the development of protection factors like base for a society of mentally healthy individuals, as well as suggests a structural change in the pattern family traditional chord with the current times subordinated to constant changes.